Pembekalan Kepemimpinan Bertajuk “Mengembangkan Kepemimpinan Anda” di KBMK POLNES Samarinda - Joko Priyono (Journal Of Social Empowerment Publications, 2024)
Development evaluates the effectiveness of the leadership training program "Developing Your Leadership" at the Christian Student Association of POLNES Samarinda. Using lecture methods, the program conveys basic leadership concepts and theories. The results indicate that the lecture method is effective in enhancing participants' understanding, confidence, and readiness to lead. Participants responded positively, noting that the material was delivered clearly and interactively. However, challenges such as limited time and resources were identified, indicating the need for a combination of other methods to provide a more comprehensive practical experience. This training emphasizes the importance of a holistic and flexible program design, as well as ongoing evaluation for the program's success. The program has significant potential in developing students' leadership skills with recommendations for future improvements.